The Nutrient Uptake Efficiency, Crop Productivity and Quality of Rice Bean in Dry Land - Lolita Endang Susilowati; Uyek Malik Yakop; Lestari Ujianto; Bambang Hari Kusumo (UNIVERSITY OF LAMPUNG, 2015)
Rice bean is a group of beans that are rich in carbohydrates, proteins and fats. This plant is resistant to pests and diseases, as well as the broad adaptability. This study aims to obtain an efficient fertilization pattern on rice bean cultivation in dry land. The treatments consisted of 9 fertilization patterns which were RP0: no fertilizer (control); RP1: 100% recommendation fertilizer (50 kg Urea and 100 kg SP-36 ha-1); RP2: 5 Mg ha-1 manure plus 50% recommendation fertilizer; RP3: RP2 plus MVA; RP4: 5 Mg ha-1 Crotalaria sp compost plus 50% recommendation fertilizer; RP5: RP4 plus VAM; RP6: 2.5 t ha-1 manure, 2.5 Mg ha-1 Crotalaria sp compost plus 50% recommendation fertilizer; RP7: 1.5 Mg ha-1 manure, 1 Mg ha-1 Crotalaria sp compost plus 50% recommendation fertilizer; RP8: RP7 plus MVA. Fertilization treatments were arranged in RCBD and each treatment was repeated 3 times. The fertilization treatments had no significant effect on NUE. Productivity of rice bean in RP3 and RP5 reached 3.75 Mg ha-1, in RP2 and RP4 achieved 2.64 Mg ha-1, and in the control treatment reached 1.94 Mg ha-1. Carbohydrate content in seeds increased by 20% in the fertilization treatments compared to the control. Protein and anthocyanin content in all treatments were not significantly different. The combination of 5 Mg organic fertilizer (manure and / or Crotalaria compost), 50% recommendation fertilizer plus MVA was an efficient fertilization pattern to improve P fertilizer uptake efficiency (PUE), productivity and quality of rice bean crop in dry land. [How to Cite: Lolita ES, UM Yakop, L Ujianto, and B Hari Kusumo. 2015. The Nutrient Uptake Efficiency, Crop Productivity and Quality of Rice Bean in Dry Land. J Trop Soils 19: 1-9. Doi: 10.5400/jts.2015.20.1.1][Permalink/DOI: www.dx.doi.org/10.5400/jts.2015.20.1.1]